Water Qualities and Eutrophication of Chanthaburi River and Laem Sing Estuary - Thaipichitburapa, Patrawut; Meksumpun, Charumas; Gunbua, Vichaya (Burapha Science Journal, 2026)
Problems of water deteriorated and eutrophication have increasingly serious in Thailand waters. The objectives of this research were study of changes in water qualities and eutrophication conditions in the Chanthaburi River and Pak Nam Laem Sing. The study was conducted 3 times in January (dry season), April (early rainy season) and July (rainy season) of year 2018. The seventeen stations were investigated, divided to 6 six stations of the river and 11 stations of estuarine zone. Our results indicated that the general water qualities were good condition, it was in Classification 2 of Surface Water Quality (PCD, 2006), the dissolved oxygen was higher than 6 mg/l. The changes in nutrients and chlorophyll a concentration was seasonal, especially silicate. The eutrophication situations in the river stations were lower level, except at the estuary during rainy season were found eutrophic levels. In addition, nutrient and chlorophyll concentrations up to 5 times higher than of eutrophic level has occurred which risking in low oxygen conditions (Hypoxia) in the water. Hence, the marine life and aquaculture might be affected by alteration of eutrophication situations. From the information obtained during this study, leading to determination the management and guideline to protect of the water resources in the future.